Factors Associated with Free Flap Viability at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Mufida Muzakkie; Argo Ismoyo; Erial Bahar (Sriwijaya Journal of Surgery, 2023)
Introduction: A free flap is part of reconstructive surgery. This technique takes tissue or bone flaps along with their original vascular supply and performs microvascular anastomosis of the pedicle arteries and veins at the recipient site. Several risk factors that influence the occurrence of flap failure are still a major concern, such as age, gender, defect size, duration of surgery, length of tissue ischemic time, nutritional status, etc. This is further associated with higher morbidity, the potential for flap failure, higher costs, and increased length of stay in the hospital. This study aimed to determine the factors associated with free flap viability at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: Cross-sectional analytic observational study. A total of 33 research subjects participated in this study. Observation of risk factors was carried out using SPSS univariate and bivariate. Results: Gender and ischemic time factors are related to free flap viability. Male gender and ischemic time < 60 minutes increase the success of free flap viability. Conclusion: Gender and length of ischemic time are associated with free flap viability at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.